2021
DOI: 10.32771/inajog.v9i2.1502
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil to Lymphocyte Ratio in Preeclampsia

Abstract: Abstract Objective: To determine the correlation between neutrophil to lymphocyte ratio and preeclampsia. To determine whether neutrophil to lymphocyte ratio can be used as a screening tool for preeclampsia.Methods: This study was conducted with a systematic review method. Articles that had been gathered and filtered were reviewed by QUADAS-2 tool. Guidelines from the American Congress of Obstetricians and Gynecologists (ACOG) and Pedoman Nasional Pelayanan Kedokteran were used as a diagnostic criteria f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Therefore, the NLR is considered as a provider of diagnostic and prognostic value in preeclampsia. [18][19][20][21][22] Mannaerts et al 10 reported that patients with preeclampsia have NLR value higher than normotensive pregnancies, although it is not significantly different. In contrast, some studies reported that the NLR value of patients with preeclampsia is significantly different compare with normotensive pregnancies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the NLR is considered as a provider of diagnostic and prognostic value in preeclampsia. [18][19][20][21][22] Mannaerts et al 10 reported that patients with preeclampsia have NLR value higher than normotensive pregnancies, although it is not significantly different. In contrast, some studies reported that the NLR value of patients with preeclampsia is significantly different compare with normotensive pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…Singhal et al 20 found that the NLR has a cutt-off value of ≥ 4.86 with a sensitivity of 68.6% and a specificity of 80.0% in predicting preeclampsia. Prasetyo et al 22 found that the NLR is associated with preeclampsia with cut-off values between 3.5-5.6 in different sensitivity and specificity. In this study, it was found a cut-off value of 4.0 with a sensitivity of 64.5% and specificity of 71%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation